The investigation and management of metal-on-metal hip arthroplasty patients - Matharu, G (2017)
Many metal-on-metal hip arthroplasties (MoMHAs) were implanted worldwide in the form of hip resurfacing arthroplasty (HRA) and total hip arthroplasty. These devices experienced unexpectedly high short-term failure rates, with many revisions performed for adverse reactions to metal debris (ARMD) and pseudotumour (a specific type of ARMD). To identify problems early, worldwide regulatory authorities recommend most MoMHA patients require regular follow-up. However these recommendations are not evidence-based and are very costly. The broad aims of this thesis were to determine the clinical impact of pseudotumour, and to develop evidence-based guidance for the investigation and management of MoMHA patients. A prospective single centre cohort of 1,429 HRAs identified pseudotumour as the commonest indication for revision surgery. The overall 15 year pseudotumour revision rate was high at 14.0%. Young females had the highest risk of pseudotumour revision, whilst males with Birmingham Hip Resurfacing (BHR) implants had the lowest risk. Two large prospective cohort studies investigated the role of blood metal ions during follow-up. Patients with BHR implants (n=494) who had blood metal ions below newly devised thresholds were at low risk of ARMD (cobalt: 2.15 μg/l for unilateral BHRs; maximum cobalt or chromium: 5.52 μg/l for bilateral BHRs). Current fixed regulatory authority thresholds missed more patients with ARMD compared with the new thresholds. These findings were subsequently validated in 416 BHR patients at two external European centres. Three observational studies investigated the role of hip imaging during follow-up. Radiographic factors predictive of HRAs with a pseudotumour included acetabular component malposition, osteolysis, and acetabular loosening. A retrospective diagnostic accuracy study demonstrated that ultrasound and magnetic resonance imaging (MRI) both had a role prior to HRA revision surgery. However combined ultrasound and MRI was most effective for both identifying and excluding intra-operative pseudotumours. Thus combined imaging may be useful in complex cases. In a prospective longitudinal cohort of 140 asymptomatic HRAs, 11% developed new pseudotumours within five years of initial assessment. No patients with a normal initial ultrasound and low blood metal ions (<2 μg/l) developed new pseudotumours (36% of hips). These patients do not need regular follow-up. Two large retrospective observational studies were performed involving MoMHA revision procedures recorded in the National Joint Registry for England and Wales. Contrary to previous observations, patients revised for ARMD had half the risk of re-revision and death compared with matched patients undergoing non-ARMD revision surgery (such as for fracture, loosening, and infection). Modifiable predictors of re-revision surgery following ARMD revision were modular component only revisions, and using ceramic-on-ceramic revision bearings. The clinical impact of pseudotumour following HRA is significant and has continued to increase into the second decade. This thesis has developed an evidence-based approach for the investigation and management of MoMHA patients. No single investigation can universally be used during patient surveillance. However important information has now been provided for risk stratifying patients for surveillance, interpreting blood metal ions, clarifying the roles of imaging, and providing parameters to safely exclude many asymptomatic patients from regular surveillance. The outcomes following ARMD revision surgery have improved since the threshold for performing revision was lowered. However outcomes were influenced by modifiable factors (type of revision procedure and bearing), suggesting that surgeons could reduce failure rates further following ARMD revision procedures.